Ability of community pharmacists to independently perform CLIA-waived testing - A multistate legal review - Joseph Doucette; Joseph Lavino (Elsevier, 2021)
The scope of practice of community pharmacy has continued in its evolution into a clinically focused profession. A critical component to pharmacist clinical offerings in the United States is the performance of Clinical Laboratory Improvement Amendments ("CLIA") waived tests. However, state laws and regulations greatly influence a pharmacist's ability to perform a CLIA-waived test. Based on this variability and lack of clarity in state laws and regulations, a legal review was performed, which focused on the following themes: 1) states which currently allow a pharmacist to independently perform CLIA-waived testing; 2) of those states, which states impose restrictions on the scope of CLIA-waived tests that may be independently performed by a pharmacist; and 3) states that impose restrictions on the ability of a pharmacist to independently perform CLIA-waived testing. Federal laws already exist that allow individuals, pursuant to certification, to perform CLIA-waived testing. This allowance presumably includes pharmacists if they follow federal law. However, some states regulate and restrict this area for pharmacists, contrary to these federal laws. States may see an improvement in patient care and further expand the practice of pharmacy by limiting restrictions on pharmacists to perform CLIA-waived tests and following federal allowances.